Good night, Lala - Calica, Corazon Ordonez (Adarna House, 2013)
"Here are eight wonderful stories of Corazon Ordonez-Calica. Set against the backdrop of wartime Pampanga are tales of enchanted stones, cathing frogs, and dodging bullets!"